POTENSI INTERAKSI OBAT PADA PASIEN HIPERTENSI DENGAN PENYAKIT PENYERTA DI RSUD PREMBUN: POTENTIAL DRUG INTERACTIONS IN HYPERTENSION PATIENTS WITH COMORBID DISEASES AT PREMBUN HOSPITAL - Kurniawati, Desi; Widiastuti, Tri Cahyani; Khuluq, Khusnul (Program Studi Farmasi-Fakultas Matematika dan Ilmu Pengetahuan Alam-Universitas Tulang Bawang, 2024)
In the treatment of hypertension accompanied by comorbidities, there are many occurrences, so the potential for polypharmacy is very large, which causes the possibility of drug interactions. Drug interactions cause various problems such as decreased therapeutic effects, increased toxicity, or altered pharmacological effects of a drug.This study aims to describe the potential interaction of hypertension drugs in inpatients at Prembun Hospital for the 2023 period. This research is descriptive research by collecting data retrospectively. Data on the use of antihypertensive drugs and data on inpatient visits were obtained from the Inpatient Institution of Prembun Hospital for the 2023 Period. Out of a total of 100 patients, there were 93 interactions (93%). There were 3 interactions, namely the most severe level, namely moderate interactions as many as 150 interactions (58.3%) occurred in drugs between Aspirin and Amlodipine, the severity of minor interactions as many as 71 interactions (27.6%) occurred between Amlodipine drugs and Furosemide, and the least severe level of drug interactions was major interactions as many as 36 interactions (14%) occurred between Spironolactone and Candesartan. From the results of the study, it can be concluded that there is 93% interaction in the use of hypertension drugs, and 7% there is no interaction in the use of hypertension drugs. Keywords: Hypertension, Comorbidities, Interaction